PENYUSUNAN BAHAN AJAR UNTUK KETRAMPILAN BERBICARA BAHASA ARAB - Khoiru Nidak (Pusat Pengembangan Bahasa IAIN Tulungagung, 2012)
One of the problems faced by teachers today is how to develop learning sources which is suitable to the students’ need and current condition of society. Since learning sources is one of the media to achieve the objective of teaching, therefore, teachers are expected to develop their creativity in constructing the sources. This article discusses theories about how to develop learning souces to teach Arabic Speaking Class.